(untitled) (The Review of Diabetic Studies, 2025)
Background: One of the major issues in the healthcare systems is patients’ readmissions to the hospitals. These readmissions are associated with worsen the patient outcomes and increase the costs of the healthcare services. Its prevalence is associated with different factors including patients demographics, their clinical conditions, and the degree of post-discharge care. The current study aimed to assess the prevalence of 30-days-hospital readmission to the internal medicine. Methodology: This is a retrospective cohort study that was conduted depending on hospital records of patients readmitted within the 30 days of discharge in the period between March 1st 2024 until 31st August 2024 from internal medicine department. The patients characteristics as age and gender, discharge clinical diagnosis, reasons for the readmission, and the outcomes of the patients including mortality were collected. Descriptive analysis and bivariate analyses were used to assess the association between demographic factors and patients outcomes. Results: The prevalence of 30-day readmission was 11 % with peaks in August 2024. The age of the patients were mostly between 74-94 years old (56.4%). The most common reasons for readmissions included penumonia, decompendated heart failure (DHF), and electrolyte imbalances. The mortality rate was 9.8 % and most of the patients were successfully discharged home (83.4%). Some diagnoses at discharge (e.g., anemia, pulmonary embolism) were significantly linked to negative outcomes, including inpatient stays and mortality. No significant association was reported between receiving home health care and readmission outcomes. Conclusion: The current study showed that older age, presence of some medical conditions as pensumonia, DHF, and electrolyte imbalance are associated with higher readmission rates and unfavorable outcomes. These results showed that those patients should have more attention before discharge through better discharge planning, infection prevention, and post-discharge monitoring that would help in reducing hospital readmissions and improve the patients’ outcomes.